In-situ construction of a NaF-rich cathode–electrolyte interface on Prussian blue toward a 3000-cycle-life sodium-ion battery. (January 2022) - Ye, Minghui; You, Shunzhang; Xiong, Jiaming; Yang, Yang; Zhang, Yufei; Li, Cheng Chao
Abstract: As a kind of high-voltage cathode for sodium-ion batteries (SIBs), the instability of a cathode–electrolyte interface (CEI) of Prussian blue (PB) results in the consumption of electrolyte and poor cycling life. Herein, an artificial NaF-rich CEI is in-situ designed on a PB cathode via a chemically presodiated strategy to remarkably prolong the cycling life of SIBs. Based on a spontaneous redox reaction between a chemical presodiation solvent and a polyvinylidene fluoride (PVDF) binder, a homogeneous, thin, and NaF-rich CEI is conformally coated on the surface of PB, forming CEI@PB. The components of CEI within CEI@PB mainly comprise inorganic Na-salts (NaF, Na2 CO3, and NaHCO3 ) and organic Na-based species (R-O-Na, R–CO–Na, and R–O2 CO–Na), which can ensure the rapid transport of Na + ions while effectively preventing CEI@PB against the attack of organic solvent and improving its cycling stability. Besides, density functional theory calculations also reveal that NaF is a good electronic insulator and ionic conductor, which is suitable as a stable CEI. Benefiting from the aforementioned merits, the CEI@PB cathode with a high areal capacity of 0.61 mAh cm −2 delivers an ultra-long cycling life of 3000 cycles. More importantly, the concept of in-situ CEI can be extended to other cathodes beyond Na batteries discussed herein. Graphical abstract: Image 1 Highlights: An artificial NaF-rich CEI is in-situ conformally coated on a PB cathode. A spontaneous redox reaction between Na and PVDF binder forms NaF-rich CEI. NaF-rich CEI can effectively prevent CEI@PB against the attack of organic solvents. CEI@PB cathode delivers an ultra-long cycling life of 3000 cycles.